FACTORS AFFECTING EARNING PER SHARE PERIOD 2013-2020 (CASE STUDY ON THE CONSUMPTION GOODS INDUSTRY PHARMACEUTICAL SUB SECTOR) - Hendrawati, Hendrawati; Murti, Wahyu; Yolanda, Yolanda (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The purpose of this study is to describe the effect of Current Ratio, Debt to equity ratio and return on equity. Receiveble Turnover (RECT), and Inventory Turnover (INVT) on Earning Per Share (EPS) partially and simultaneously in pharmaceutical companies that go public. The type of research used is associative research. Sources of data used in this study is secondary data. Secondary data in this study are financial statements of 3 sample companies selected in this study, namely At Kimia Farma (Persero) Tbk, Indofarma (Persero) in the period 2013 – 2020. In this study, a purposive sampling technique was used where the sample is taken based on clear criteria reasons. The data analysis technique used in this research is descriptive analysis (descriptive statistics), unit root test, simple linear regression, and multiple linear regression. The results of this study stated that the Current Ratio, Debt to equity ratio and return on equity. Receivable Turnover (RECT), and Inventory Turnover (INVT) to Earning Per Share (EPS) have a significant effect simultaneously and partially on Earning Per Share (EPS).